Tollins 2 : dynamite tales - Iggulden, Conn (Harper, 2011)
Life for the Tollins in idyllic Chorleywood has been turned upside down ever since the humans built a fireworks factory and started using Tollins as industrial supplies. Now renegade Tollin Sparkler is back for more danger, adventure, and hilarity.